Applications of Carbon Nanotubes in Biotechnology and Biomedicine - Bekyarova, Elena (2005)
Due to their electrical, chemical, mechanical and thermal properties, carbon nanotubes are one of the most promising materials for the electronics, computer and aerospace industries. Here, we discuss their properties in the context of future applications in biotechnology and biomedicine. The purification and chemical modification of carbon nanotubes with organic, polymeric and biological molecules are discussed. Additionally we review their uses in biosensors, assembly of structures and devices, scanning probe microscopy and as substrates for neuronal growth. We note that additional toxicity studies of carbon nanotubes are necessary so that exposure guidelines and safety regulations can be established in a timely manner.